Preparation of magnetic microcapsules of α-amylase and α-glucosidase for dual-target affinity screening of active components from Toona sinensis. (January 2023) - Guo, Shuang; Meng, Jing; Wang, Shuai; Gu, Dongyu; Chu, Tingting; Yang, Yi
Abstract: Natural products are an important source of drug development and have good prospects in the treatment of many diseases. However, the efficacy of many natural drugs is achieved through multi-targets, which poses a huge obstacle to their development. In this study, a bienzyme microcapsule system based on α-amylase and α-glucosidase was constructed for the ligand fishing of natural compounds. The microcapsules were formed on the surface of calcium carbonate particles by self-polymerization of dopamine, which physically encapsulated iron oxide and α-glucosidase. Then, α-amylase was immobilized on the surface of magnetic material with glutaraldehyde as crosslinking agent, and calcium carbonate template was removed by EDTA to form a bienzyme system for affinity screening of active components from Toona sinensis . The results showed that two compounds, 1, 2, 3, 4, 6-penta-O-galloyl-β-D -glucose and quercitrin were affinity screened from the extracts of Toona sinensis . In vitro activity experiment proved that they were α-amylase and α-glucosidase inhibitors, respectively. Moreover, both of them were mixed type inhibitors that can interact with active centers of corresponding enzymes through multiple hydrogen bonds, van der Waals forces, etc. This study not only proved the effectiveness of the bienzyme system, but also provided a successful example for multi-target screening of natural products. Graphical Abstract: ga1 Highlights: Bifunctional microcapsules of α-amylase and α-glucosidase was constructed. Active components were dual-target affinity screened by microcapsules. Interactions between targets and active compounds were studied by molecular docking.